PERAN POSYANDU DALAM MENINGKATKAN KUALITAS KESEHATAN IBU DAN ANAK DI DESA POLOSIRI KECAMATAN BAWEN KABUPATEN SEMARANG 2024 - Abidin, Zaenal; Putri Camilla (Tahta Media Grup, 2023)
The aim of this service through socialization is to increase the role of Posyandu in improving the quality of maternal and child health in Polosiri Village, Bawen District, Semarang Regency. Participants in this socialization are mothers and children who actively participate in Posyandu activities in Polosiri Village. This service was carried out at the Polosiri Village Hall on February 1 2024. The research results show that Posyandu has a significant role in improving the quality of maternal and child health in the area. Through routine activities such as health checks, nutritional education, immunizations, and monitoring children's growth, Posyandu is able to provide quality education and health services to the local community. The role of posyandu in preventing stunting is very significant in reducing stunting rates in children. Therefore, this socialization provides an important contribution in understanding how the role of posyandu can effectively improve the quality of maternal and child health in Polosiri Village, Bawen District, Semarang Regency. The obstacle factor that occurred during the research was that there were some parents who did not understand the importance of preventing stunting from an early age.